Pigmented Villonodular Synovitis Treated as Spondyloarthritis for Four Years- A Case Report - Hassan, Md Masudul; Islam, Md Ekramul; Islam, Md Nazrul; Ahmedullah, Abul Khair; Hasan, Md Nazmul (Bangladesh Medical Journal, 2019)
Pigmented villonodular synovitis (PVNS) is a rare disorder where abnormal synovial proliferation and insidious swelling are the characteristic features. As insidious joint swelling has many common causes and PVNS is rare entity, so that it may be missed or under evaluated. Here inconclusive biopsy findings at an early stage and features resembling spondyloarthritis (SpA) delayed the diagnosis. A 28-year-old young man presented with insidious swelling of knee. Here repeated aspiration and synovial fluid analysis with routine serological and radiological examination were inconclusive. Then he was labeled and treated as spondyloarthritis (SpA) for four years without improvement. After four years of sufferings he admitted here and reached the diagnosis of PVNS with the help of MRI and synovial biopsy. Sometimes rare disease diagnosis is complicated by the absence of typical features and inconclusive reports. Common differentials may mimic the diagnosis and rare disease may loss the attention. Here PVNS was treated as SpA for four years before being diagnosed. Bangladesh Med J. 2017 May; 46 (2): 53-55